If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3 = 7(x + 2) + -3x Reorder the terms: 3 + 3x = 7(x + 2) + -3x Reorder the terms: 3 + 3x = 7(2 + x) + -3x 3 + 3x = (2 * 7 + x * 7) + -3x 3 + 3x = (14 + 7x) + -3x Combine like terms: 7x + -3x = 4x 3 + 3x = 14 + 4x Solving 3 + 3x = 14 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 3 + 3x + -4x = 14 + 4x + -4x Combine like terms: 3x + -4x = -1x 3 + -1x = 14 + 4x + -4x Combine like terms: 4x + -4x = 0 3 + -1x = 14 + 0 3 + -1x = 14 Add '-3' to each side of the equation. 3 + -3 + -1x = 14 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 14 + -3 -1x = 14 + -3 Combine like terms: 14 + -3 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 60y^2-540=0 | | 6x-21y=0 | | 9=2L+2W | | 3y+5=25-y | | -5(z+8)-(-8z-3)=2z | | 243-61m=882 | | 3x+7=17-6x | | x+14=5x+30 | | 18x+54y+110z=500 | | -15x=-45 | | a=yn+y | | 4-3x=-2x-1 | | 4(x+2)-2(x-4)=16+2(x-6) | | 3(x-6)=-12+3(x-2) | | mp+mv=t | | (2x+1)(x+9)=9 | | -9x+7=4x+1 | | 3(x+2)-6=24 | | 5+8x=3x+15 | | 50x^2+20x-16=0 | | 6+0.10x=.15x+8 | | 9x-6y=30 | | -(3x-5)-(2x-6)+1=-5(x-1)-(3x+2)+3 | | 8x(7-24)=32 | | 8x(7-24)= | | -2p+120=3p+20 | | 0.5+0.05x=9.8 | | (x-3)(x^2+3x+9)=98 | | 0.5+0.05x=9.6 | | 3x=x+45 | | -14579x-63903= | | 1363x-15942x= |